Imagens precárias: inscrições tênues de violência ditatorial no Brasil - Márcio Seligmann-Silva (Estudos de Literatura Brasileira Contemporânea)
This text presents a reflexion on the difficulties of the inscription of the Brazilian civil-military dictatorship (1964-1985) and its violent stories. It develops an analysis of the precarious character of those inscriptions, which have to deal with an absence of eco in the public sphere. A privatization of the memory work blocs the mourning and the juridical elaboration of the terrible facts of that period. The author tries to show the strategies of presentation of this past and its tough inscription departing from the works of artists (as Rosângela Rennó), photographers and novelists (as Renato Tapajós and Urariano Mota).